Isokinetic imbalance of adductor-abductor hip muscles in professional soccer players with chronic adductor-related groin pain - Belhaj, K.; Meftah, A.; Mahir, L.; Lmidmani, F.; Elfatimi, A. (European Journal of Sport Science, 2016)
This study aims to compare the isokinetic profile of hip abductor and adductor muscle groups between soccer players suffering from chronic adductor-related groin pain (ARGP), soccer players without ARGP and healthy volunteers from general population. Study included 36 male professional soccer players, who were randomly selected and followed-up over two years. Of the 21 soccer players eligible to participate in the study, 9 players went on to develop chronic ARGP and 12 players did not. Ten healthy male volunteers were randomly selected from the general population as a control group. Comparison between the abductor and adductor muscle peak torques for players with and without chronic ARGP found a statistically significant difference on the dominant and non-dominant sides (p < .005), with the abductor muscle significantly stronger than the adductor muscle. In the group of healthy volunteers, the adductor muscle groups were significantly stronger than the abductor muscle groups on both dominant and non-dominant sides (p < .05). For the group of players who had developed chronic ARGP, abductor-adductor torque ratios were significantly higher on the affected side (p = .008). The adductor muscle strength was also significantly decreased on the affected side. This imbalance appears to be a risk factor for adductor-related groin injury. Therefore, restoring the correct relationship between these two agonist and antagonist hip muscles may be an important preventative measure that should be a primary concern of training and rehabilitation programmes.